2017
DOI: 10.11598/btb.2017.24.1.550
|View full text |Cite
|
Sign up to set email alerts
|

ISOLATION AND CHARACTERIZATION OF A MOLYBDENUM-REDUCING AND PHENOLIC- AND CATECHOL-DEGRADING Enterobacter sp. STRAIN SAW-2

Abstract: Molybdenum is an emerging pollutant worldwide. The objective of this study is to isolate molybdenum-reducing bacterium with the ability to grow on phenolic compounds (phenol and catechol). The screening process was carried out on a microplate. The bacterium reduced molybdenum in the form of sodium molybdate to molybdenum blue (Mo-blue). The bacterium required a narrow pH range for optimal reduction of molybdenum, i.e. between pH 6.3 and o 6.8, with temperature between 34 and 37 C. Molybdate reduction to Mo-blu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The preferability of simple sugars such as glucose and sucrose in Mo reduction m also be because Mo reduction is growth-associated; therefore, the use of easily assimi sugar is more favourable [6]. In comparison with a study by Ahmad et al [7] using domonas sp. strain DRY1 isolated from Antarctic soil, glucose was the best electron d while Darham et al [17] reported that Mo-reducing Antarctic marine bacterium Ma monas sp.…”
Section: Carbon Source Concentrationmentioning
confidence: 92%
See 3 more Smart Citations
“…The preferability of simple sugars such as glucose and sucrose in Mo reduction m also be because Mo reduction is growth-associated; therefore, the use of easily assimi sugar is more favourable [6]. In comparison with a study by Ahmad et al [7] using domonas sp. strain DRY1 isolated from Antarctic soil, glucose was the best electron d while Darham et al [17] reported that Mo-reducing Antarctic marine bacterium Ma monas sp.…”
Section: Carbon Source Concentrationmentioning
confidence: 92%
“…Ahmad et al [8] stated that (NH 4 ) 2 SO 4 is an easily assimilable nitrogen source along with two ammonium ions to be used. Furthermore, its availability to be commonly utilised by bacteria and affordable for practical bioremediation have made (NH 4 ) 2 SO 4 a good nitrogen source [7]. Previous work on Marinomonas sp.…”
Section: Nitrogen Sources and Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…In Malaysia, the National Guidelines for Drinking Water Quality Standard is 0.002 mg/L and the 2014 Environmental Quality Report demonstrated that nearly all of the groundwater observing stations had exceeded this level for phenol. This is due to phenol and phenolic substances are the number one scheduled waste product in Malaysia as their usage in the industrial sector is one of the highest (Ahmad et al, 2011a(Ahmad et al, , 2012(Ahmad et al, , 2017Arif et al, 2013;Department of Environmental, 2014;Gami et al, 2014b;AbdEl-Mongy et al, 2015;Norazah et al, 2015;Sabullah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%